Determinants of Transfer Pricing Decisions in Mining Companies Listed on the Indonesian Stock Exchange - Ade Maya Saraswati (Jurnal Economia, 2021)
Abstract: This research aims to analyse the effect of tax and tunnelling incentive to transfer pricing with good corporate governance as a moderating variable. This research focuses on all mining companies listed on the Indonesian Stock Exchange in the period from 2014-2018 by using the purposive sampling technique to determine the sample. There are 90 data observations used as the sample and analysed by using logistic regression and moderation regression analysis, with the help of the SPSS 20 program. The research result shows that tax has a positive effect on the decision of transfer pricing; tunnelling incentive does not have an effect on the decision of transfer pricing. Good corporate governance moderates the effect of tax to transfer pricing, meanwhile good corporate governance does not moderate the effect of tunnelling incentive to the decision of transfer pricing. Keywords: Good corporate governance; Tax; Transfer pricing; Tunnelling incentive Determinan Keputusan Transfer Pricing pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek IndonesiaAbstrak: Penelitian ini bertujuan untuk menganalisis pengaruh pajak dan tunnelling incentive terhadap transfer pricing dengan good corporate governance sebagai variabel pemoderasi. Populasi dari penelitian ini adalah seluruh perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia tahun 2014-2018 dengan penentuan sampel menggunakan teknik purposive sampling. Sampel dalam penelitian berjumlah 90 observasi data yang kemudian dianalisis menggunakan regresi logistik dan analisis regresi moderasi dengan bantuan program SPSS 20. Hasil penelitian menunjukkan bahwa pajak berpengaruh positif terhadap keputusan transfer pricing, tunneling incentive tidak berpengaruh terhadap keputusan transfer pricing, good corporate governance memoderasi pengaruh pajak terhadap transfer pricing, sedangkan good corporate governance tidak memoderasi pengaruh tunnelling incentive terhadap keputusan transfer pricing.Kata kunci: Good corporate governance; Pajak, Transfer pricing, Tunnelling incentive